2019
DOI: 10.1001/jamaneurol.2018.4410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Care and In-Hospital Outcomes of Asian American and White Patients With Acute Ischemic Stroke

Abstract: IMPORTANCE Although overall stroke incidence and mortality in the United States is improving, little is known about the characteristics and clinical outcomes of acute ischemic stroke in Asian American individuals.OBJECTIVE To compare the characteristics, care, and outcomes of Asian American and white patients with acute ischemic stroke. DESIGN, SETTING, PARTICIPANTS Retrospective analysis of Asian American and white patients admitted with a primary diagnosis of acute ischemic stroke to hospitals participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…Non-Western immigrants were younger at stroke diagnosis than Western immigrants and Danish-born individuals. Our results clearly corroborate previous studies in the UK and the USA reporting that Black British 24 and Asian Americans 25 experience early onset of stroke. A Danish study on uptake of cardiac rehabilitation and preventive medications after acute coronary syndrome showed that non-Western immigrants had a 50% to 75% higher risk of discontinuing various preventive medications, which could be seen as one of the possible explanations for early stroke onset in this population.…”
Section: Discussionsupporting
confidence: 92%
“…Non-Western immigrants were younger at stroke diagnosis than Western immigrants and Danish-born individuals. Our results clearly corroborate previous studies in the UK and the USA reporting that Black British 24 and Asian Americans 25 experience early onset of stroke. A Danish study on uptake of cardiac rehabilitation and preventive medications after acute coronary syndrome showed that non-Western immigrants had a 50% to 75% higher risk of discontinuing various preventive medications, which could be seen as one of the possible explanations for early stroke onset in this population.…”
Section: Discussionsupporting
confidence: 92%
“…A study of the Get With The Guidelines-Stroke registry reported that for patients ≤40 years of age with acute ischemic stroke hospitalized between January 2009 and September 2015, thrombolysis use was higher than those over 40 years of age (32). A retrospective analysis of Asian American and white patients admitted with a primary diagnosis of acute ischemic stroke to hospitals participating in the Get With The Guidelines-Stroke (GWTG-Stroke) program between 2004 and 2016 showed that Asian Americans were less likely to receive thrombolysis treatment (0.95, p = 0.003) even though the strokes were more severe (33). Findings from the (Florida-Puerto Rico Collaboration to Reduce Stroke Disparities) registry for the time period 2020-2015 showed that among patients with mild stroke, disparities existed in thrombolysis treatment for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, about 22 million people around the world suffer from stroke, mainly including 3 categories: ischemic (87%), hemorrhagic (10%), and subarachnoid hemorrhage (3%). [ 1 ] Sixty percent of acute ischemic stroke (AIS) is caused by thrombosis, and 40% is caused by embolism. The lifetime risk of stroke for patients aged 55 to 75 years is 20% in women and 15% in men.…”
Section: Introductionmentioning
confidence: 99%